Mayahuelin, a Type I Ribosome Inactivating Protein: Characterization, Evolution, and Utilization in Phylogenetic Analyses of Agave - Lledías, Fernando; Gutiérrez, Jesús; Martínez-Hernández, Aída; García-Mendoza, Abisaí; Sosa, Eric; Hernández-Bermúdez, Felipe; Dinkova, Tzvetanka D.; Reyes, Sandi; Cassab, Gladys I.; Nieto-Sotelo, Jorge (Frontiers in Plant Science, 2020)
Agaves resist extreme heat and drought. In A. tequilana var. azul, the central spike of the rosette -containing the shoot apical meristem and folded leaves in early stages of development- is remarkably heat tolerant. We found that the most abundant protein in this organ is a 27 kDa protein. This protein was named mayahuelin to honor Mayáhuel, the agave goddess in the Aztec pantheon. LC-MS/MS analyses identified mayahuelin as a type I RIP (Ribosome Inactivating Protein). In addition to the spike, mayahuelin was expressed in the peduncle and in seeds, whereas in mature leaves, anthers, filaments, pistils, and tepals was absent. Anti-mayahuelin antibody raised against the A. tequilana var. azul protein revealed strong signals in spike leaves of A. angustifolia, A. bracteosa, A. rhodacantha, and A. vilmoriniana, and moderate signals in A. isthmensis, A. kerchovei, A. striata ssp. falcata, and A. titanota, indicating conservation at the protein level throughout the Agave genus. As in charybdin, a type I RIP characterized in Drimia maritima, mayahuelin from A. tequilana var. azul contains a natural aa substitution (Y76D) in one out of four aa comprising the active site. The RIP gene family in A. tequilana var. azul consists of at least 12 genes and Mayahuelin is the only member encoding active site substitutions. Unlike canonical plant RIPs, expression of Mayahuelin gene in S. cerevisiae did not compromise growth. The inhibitory activity of the purified protein on a wheat germ in vitro translation system was moderate. Mayahuelin orthologs from other Agave species displayed one of six alleles at Y76: (Y/Y, D/D, S/S, Y/D, Y/S, D/S) and proved to be useful markers for phylogenetic analysis. Homozygous alleles were more frequent in wild accessions whereas heterozygous alleles were more frequent in cultivars. Mayahuelin sequences from different wild populations of A. angustifolia and A. rhodacantha allowed the identification of accessions closely related to azul, manso, sigüín, mano larga, and bermejo varieties of A. tequilana and var. espadín of A. angustifolia. Four A. rhodacantha accessions and A. angustifolia var. espadín were closer relatives of A. tequilana var. azul than A. angustifolia wild accessions or other A. tequilana varieties